2018
DOI: 10.1186/s13578-018-0216-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA KCNQ1OT1 promotes osteogenic differentiation to relieve osteolysis via Wnt/β-catenin activation

Abstract: BackgroundResveratrol (RSV) has been reported to stimulate osteoblast differentiation in which Wnt/β-catenin signaling pathway played a crucial role. However, whether and how RSV activated Wnt/β-catenin pathway in osteogenic differentiation still remained elusive.MethodsIn vivo polymethylmethacrylate (PMMA) particle-induced osteolysis (PIO) mouse model and in vitro PMMA particle-stimulated mouse mesenchymal stem cells (mMSCs) experiments were established. Relative expression levels of lncRNA KCNQ1OT1, β-cateni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 31 publications
(34 reference statements)
2
45
1
Order By: Relevance
“…[25][26][27][28] Previous research demonstrated that KCNQ1OT1 increases beta-catenin protein level and its transcriptional activity in osteoblast cells. 16 We investigated in the present research whether KCNQ1OT1 was involved in osteosarcoma development. Our data for the rst time demonstrated a signicant increase in KCNQ1OT1 expression level in osteosarcoma and its association with osteosarcoma progression.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…[25][26][27][28] Previous research demonstrated that KCNQ1OT1 increases beta-catenin protein level and its transcriptional activity in osteoblast cells. 16 We investigated in the present research whether KCNQ1OT1 was involved in osteosarcoma development. Our data for the rst time demonstrated a signicant increase in KCNQ1OT1 expression level in osteosarcoma and its association with osteosarcoma progression.…”
Section: Discussionmentioning
confidence: 95%
“…14,15 A previous research by Gao et al demonstrated that overexpressing KCNQ1OT1 in osteoblast cells might increase beta-catenin expression and its activity, presumably by binding to beta-catenin. 16 Beta-catenin is a transcription co-activator, complexing with TCF/LEF family transcription factors to activate the transcription of target genes such as MYC, JUN, WISP1 and CCND1 that are involved in cell proliferation, survival and mobility. 17,18 Activation of WNT/beta-catenin signaling pathway has been demonstrated to promote osteosarcoma cell proliferation, metastasis and chemoresistance, and inhibition of this osteosarcoma-promoting pathway might synergize with current therapeutic approaches and improve patients' outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, JNK is closely related to the reorganization of the actin cytoskeleton, which is essential for chondrogenic differentiation (24). Other investigations reported that β‐catenin‐related signaling pathways, such as the canonical Wnt/ β‐catenin and PI3K/Akt/GSK‐3β/β‐catenin pathways, are involved in the osteogenic differentiation of MSCs (25, 26). On the basis of this evidence, it is reasonable to deduce that the up‐regulation of phospho‐JNK and suppression of β‐catenin may be closely associated with the prochondrogenic and antiossific effects of KGN preconditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, lncRNAs are pivotal regulatory molecules that are involved in diverse biological processes, including cell proliferation, cell-cycle progression, epithelial-mesenchymal transition (Cen et al, 2018), apoptosis (Y. Guo, Hu, Hu, He, & Li, 2018), differentiation (Gao, Ge, Li, Zhou, & Xu, 2018), and chromosome inactivation (Yue & Ogawa, 2018 (Hu, Jiang, & Jiang, 2017). Besides, the importance of lncRNA ANRIL in other diseases, like atherosclerosis (Chi et al, 2017) and diabetic retinopathy (Thomas, Feng, & Chakrabarti, 2017), have also been gradually reported.…”
Section: Discussionmentioning
confidence: 99%